Social inclusion of academic library in realising Sustainable Development Goals (SDGs) through Corporate Social Responsibility (CSR) program: a case study in Tengku Anis Library UiTM Kelantan / Della Kartika Sari ... [et al.] - Sari, Della Kartika; Soesantari, Tri; Fahmi, Faisal; Atmi, Ragil Tri (Faculty of Information Management, 2023)
Academic libraries do not have an awareness of being proactive in the community to organise programmes to increase the role of libraries in fulfilling broad information needs. Role of the academic libraries to support high quality education in society of community service can be realised through the Corporate Social Responsibility (CSR) programme which is a form of library social inclusion. The impact of the realisation of the library's social inclusion through CSR programmes on the community is the implementation of the Sustainable Development Goals (SDGs). Research conducted on libraries in several countries shows that libraries, both public libraries and academic libraries, through CSR programmes can realise the SDGs, especially the first, second, third, fourth, seventh, and thirteenth points. This research uses a qualitative method based on a case study of the CSR Program implemented by the Tengku Anis Library UiTM Kelantan and support by literature review relevant to the program. The informants for the research were the program implementers and program recipients from Pangkal Meleret Vocational School and the Lilbanat Darulnaim Machang Orphanage. Based on the activities of Tengku Anis Library (PTA) as one of the academic libraries, it contributes to the realisation of the Sustainable Development Goals (SDGs), especially on the fourth point of quality education through its CSR programmes. Based on this finding, academic libraries in other countries can implement similar Corporate Social Responsibility (CSR) programmes in order to realise the achievement of Sustainable Development Goals (SDGs). Implementation of CSR programs from libraries can focus on literacy programs for the community to increase knowledge and education.